2006
DOI: 10.1021/jo061234p
|View full text |Cite
|
Sign up to set email alerts
|

A General and Efficient FeCl3-Catalyzed Nucleophilic Substitution of Propargylic Alcohols

Abstract: A general and efficient FeCl3-catalyzed substitution reaction of propargylic alcohols with carbon- and heteroatom-centered nucleophiles such as allyl trimethylsilane, alcohols, aromatic compounds, thiols, and amides, leading to the construction of C-C, C-O, C-S and C-N bonds, has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
93
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(93 citation statements)
references
References 15 publications
0
93
0
Order By: Relevance
“…In 2006, Zhan et al [26] developed an efficient and general FeCl 3 -catalyzed nucleophilic substitution of propargylic alcohols by using various nucleophiles including many C(sp 2 )-centered nucleophiles. In 2007, Jana et al [27] reported an FeCl 3 -catalyzed selective 3-C alkylation of indoles with benzylic alcohols.…”
Section: Methodsmentioning
confidence: 99%
“…In 2006, Zhan et al [26] developed an efficient and general FeCl 3 -catalyzed nucleophilic substitution of propargylic alcohols by using various nucleophiles including many C(sp 2 )-centered nucleophiles. In 2007, Jana et al [27] reported an FeCl 3 -catalyzed selective 3-C alkylation of indoles with benzylic alcohols.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have developed a highly efficient iron-A C H T U N G T R E N N U N G (III)-or bismuthA C H T U N G T R E N N U N G (III)-catalyzed propargylic substitution of propargylic alcohols or acetates with various heteroatom-and carbon-centered nucleophiles, [8] where the allylsilane as the carbon-centered nucleophile is the exclusive example for the construction of sp 3 -sp 3 C À C bonds. Naturally we attempted to extend the scope of carbon-centered nucleophiles from allylsilanes to ketones or enoxysilanes for the formation of g-alkynyl ketones.…”
Section: (Propargyl)]mentioning
confidence: 99%
“…[2] Reactions of this type have been traditionally carried out using the Nicholas reaction but with some drawbacks: more than a stoichiometric amount of [Co 2 (CO) 8 ] is required, and several steps are necessary to obtain the propargylic product from propargylic alcohols via cationic propargylic complexes [Co 2 (CO) 6 …”
mentioning
confidence: 99%
“…74 The allylic alkylation represents an important transformation in organic chemistry and different metal processes have been described for this reaction. Direct allylation of alcohols [75][76][77][78][79][80][81][82][83] using allyltrimethylsilane for C-C bond formation in the presence of Lewis acid as a catalyst has attracted the interest of the researchers 35 and some results are shown in Table 9. Heterobimetallic 'Pd-Sn' catalyst was used for the direct alkylation of arenes, heteroarenes, 1,3-dicarbonyls and organosilicon nucleophiles with allylic / propargylic / benzylic alcohols in MeNO 2 .…”
mentioning
confidence: 99%
“…92 Furthermore, alkylation of furans by benzyl, allyl, and propargyl alcohols 80,[93][94][95][96] in the presence of Lewis acids as a catalyst has been also reviewed 17 and of the many results a selection is shown in Table 11. The catalytic nucleophilic substitution of tertiary alcohols of type 15, using carbon or heteroatom based nucleophiles in the presence of Lewis acid has been the several publications 79,85,98,99 as well as a review 20 and selected results are shown in Table 12. Tables 13 and 14 respectively.…”
mentioning
confidence: 99%